The Potential Health Benefits of Gallic Acid: Therapeutic and Food Applications - Milad Hadidi; Rafael Liñán-Atero; Mohammad Tarahi; Marios C. Christodoulou; Fatemeh Aghababaei (MDPI AG, 2024)
Gallic acid (GA), a phenolic acid found in fruits and vegetables, has been consumed by humans for centuries. Its extensive health benefits, such as antimicrobial, antioxidant, anticancer, anti-inflammatory, and antiviral properties, have been well-documented. GA's potent antioxidant capabilities enable it to neutralize free radicals, reduce oxidative stress, and protect cells from damage. Additionally, GA exerts anti-inflammatory effects by inhibiting inflammatory cytokines and enzymes, making it a potential therapeutic agent for inflammatory diseases. It also demonstrates anticancer properties by inhibiting cancer cell growth and promoting apoptosis. Furthermore, GA offers cardiovascular benefits, such as lowering blood pressure, decreasing cholesterol, and enhancing endothelial function, which may aid in the prevention and management of cardiovascular diseases. This review covers the chemical structure, sources, identification and quantification methods, and biological and therapeutic properties of GA, along with its applications in food. As research progresses, the future for GA appears promising, with potential uses in functional foods, pharmaceuticals, and nutraceuticals aimed at improving overall health and preventing disease. However, ongoing research and innovation are necessary to fully understand its functional benefits, address current challenges, and establish GA as a mainstay in therapeutic and nutritional interventions.